A case report of a spherical mass in the right atrium: myxoma or thrombus? - Wu, Yulian; Wang, Xidan; Yang, Daoling; Tao, Xiaoying (Frontiers in Oncology, 2025)
BackgroundIntracardiac masses encompass a spectrum of pathologies, including tumors, thrombi, and other proliferative lesions, with left atrial involvement being more common than right atrial involvement. In particular, spherical thrombi in the right atrium are exceedingly rare. Diagnostic evaluation relies on modalities such as transesophageal echocardiography (TEE), cardiac magnetic resonance imaging (CMR), and multidetector computed tomography (MDCT). TEE provides detailed information regarding the mass’s location, number, size, and mobility, while CMR and MDCT offer insights into tissue characterization. In this report, we describe a case in which both TEE and CMR misdiagnosed a spherical thrombus as a myxoma. By analyzing the features of TEE and CMR, we summarize the reasons for this misdiagnosis, aiming to serve as a cautionary reminder for clinicians.Case summaryWe report a case of a 59-year-old male, whose past medical history was notable only for a childhood lower extremity trauma (details unknown and not requiring hospitalization or treatment) and no history of diabetes, hypertension, prolonged immobilization, or familial diseases. A spherical mass was incidentally detected in the right atrium during a routine examination. Initial transesophageal echocardiography (TEE), including three-dimensional imaging, revealed a hyperechoic mass with a distinct stalk attached to the interatrial septum near the inferior vena cava, findings that were initially interpreted as consistent with a myxoma. However, subsequent surgical resection and histopathological analysis demonstrated fibrous tissue proliferation and collagenization, confirming the lesion as a thrombus. The unique spherical configuration and its location underscore the potential for misdiagnosis when relying solely on conventional imaging modalities.ConclusionRight atrial thrombi are rare findings observed on echocardiography. This case illustrates an incidental spherical thrombus located near the inferior vena cava entrance at the top of the right atrium. The echocardiographic features of this thrombus can resemble those of a myxoma, necessitating careful differentiation through additional examinations. In this case, the misdiagnosis on TEE was attributed to the mass displaying slightly increased echogenicity, a narrow attachment to the right atrium near the inferior vena cava, and a degree of mobility. Typically, thrombi appear hypoechoic; however, the slightly elevated echogenicity observed here may be due to the chronicity of thrombus formation, which could also account for the narrow attachment. According to the PLACE-T scoring system, the following points were assigned:P (Patient history): 0 points.L (Lobulation): Lobulated contour, 0 points.Attachment site width: Narrow stalk (base diameter/maximal diameter <0.3), +2 points.Clinical context: No relevant medical history, 0 points.Echogenicity pattern: Heterogeneous echogenicity, +1 point.T (Tissue characterization): No specific features, 0 points.With a total score of 3 points, the probability of a thrombus is high (sensitivity 92% and specificity 85% for scores ≤3). When TEE is not feasible or yields uncertain findings, other non-invasive imaging modalities such as multi-slice spiral CT (MDCT) or cardiac magnetic resonance imaging (CMR) may be considered. Although these techniques are predominantly used for left atrial assessment—MDCT, for instance, can successfully identify left atrial thrombus with a negative predictive value of 100% and a positive predictive value ranging from 41% to 92%—the accuracy of differentiating right atrial masses remains uncertain. Therefore, in similar cases, it is imperative to integrate the patient’s clinical history, multiple auxiliary examination results, and the PLACE-T score rather than relying solely on the features observed on TEE.